2023
DOI: 10.3390/ijms24065559
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Single Whole-Body Cryostimulation on Cytokine Status and Oxidative Stress Biomarkers during Exhaustive Physical Effort: A Crossover Study

Abstract: The purpose of the study was to assess the impact of single whole-body cryostimulation (WBC) preceding submaximal exercise on oxidative stress and inflammatory biomarkers in professional, male athletes. The subjects (n = 32, age 25.2 ± 37) were exposed to low temperatures (−130 °C) in a cryochamber and then participated in 40 min of exercise (85% HRmax). Two weeks afterwards, the control exercise (without WBC) was performed. Blood samples were taken before the start of the study, immediately after the WBC proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it was confirmed that the enzymatic activity of erythrocytes measured after exercise preceded by exposure to extremely low temperatures was statistically significantly lower compared to that observed after control exercise. SOD and GPx activity was higher in erythrocytes when exercise was not preceded by cryostimulation [38].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, it was confirmed that the enzymatic activity of erythrocytes measured after exercise preceded by exposure to extremely low temperatures was statistically significantly lower compared to that observed after control exercise. SOD and GPx activity was higher in erythrocytes when exercise was not preceded by cryostimulation [38].…”
Section: Discussionmentioning
confidence: 90%
“…Completely different but most commonly used WBC and CWS standard protocols are presented [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…A comprehensive analysis of WBC effects on muscle hypertrophy and anabolic processes is warranted [47]. Exploring novel strategies that incorporate WBC prior to exercise could reveal its timing-dependent efficacy in promoting muscle repair and growth [48]. Such strategies may also offer insights into how WBC could modulate mTOR kinase pathways, potentially priming the musculoskeletal system against exercise-induced stress [49].…”
Section: Discussionmentioning
confidence: 99%
“…Using well-trained athletes, Jureka et al proved that a single WBC session effectively modulated the cytokine profile after intensive exercise. This may suggest that even a single exposure to very low temperatures may normalize the body’s inflammatory response to exercise [ 13 ]. This effect is statistically supported by the correlations between the level of cytokines and oxidative stress markers in the blood of these subjects, both after leaving the cryochamber and after the exercise preceded by WBC.…”
mentioning
confidence: 99%
“…This could corroborate the relationship between ROS production and the modulation of the inflammatory response that normally occurs after vigorous exercise. This response, which can sometimes be negative on recovery from muscle damage, could be mitigated using this type of strategic approach [ 13 ].…”
mentioning
confidence: 99%